2020
DOI: 10.1038/s41598-020-65098-7
|View full text |Cite
|
Sign up to set email alerts
|

Increasing carbohydrate oxidation improves contractile reserves and prevents hypertrophy in porcine right heart failure

Abstract: In heart failure, myocardial overload causes vast metabolic changes that impair cardiac energy production and contribute to deterioration of contractile function. However, metabolic therapy is not used in heart failure care. We aimed to investigate the interplay between cardiac function and myocardial carbohydrate metabolism in a large animal heart failure model. Using magnetic resonance spectroscopy with hyperpolarized pyruvate and magnetic resonance imaging at rest and during pharmacological stress, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…Only few studies have probed acid-base disturbances in altered physiology or disease. Recently, we confirmed the finding from Lau et al that hyperpolarized [1-13 C]pyruvate detects myocardial acidification during increased workload from dobutamine stress (21,31). In the same paper, we reported that heart failure from right ventricular volume overload decreased myocardial pH in-vivo.…”
Section: Hyperpolarized Ph-imaging Of the Heartsupporting
confidence: 90%
See 3 more Smart Citations
“…Only few studies have probed acid-base disturbances in altered physiology or disease. Recently, we confirmed the finding from Lau et al that hyperpolarized [1-13 C]pyruvate detects myocardial acidification during increased workload from dobutamine stress (21,31). In the same paper, we reported that heart failure from right ventricular volume overload decreased myocardial pH in-vivo.…”
Section: Hyperpolarized Ph-imaging Of the Heartsupporting
confidence: 90%
“…Apart from technical developments, one critical question remains: Where does pH-imaging fit in the clinic, and which patients may benefit from the technique? Only three studies have investigated the technique in disease models (28,29,31). More are needed to elucidate its potential across the field of cardiology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolic remodeling is closely related to the occurrence and development of cardiac hypertrophy and other heart diseases. Exploring the energy metabolism mechanism of cardiomyocytes may lead to new therapeutic targets, which will be helpful to design new effective methods and strategies for the treatment of heart failure ( Bøgh et al., 2020 ; Makrecka-Kuka et al., 2020 ; Zuurbier et al., 2020 ). As we all know, physical exercise has a protective effect on the heart, and can even partially compensate for heart damage and improve heart function.…”
Section: Discussionmentioning
confidence: 99%